A Thermoelectric Generator Replacing Radiator for Internal Combustion Engine Vehicles - Nyambayar Baatar; Shiho Kim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
We have proposed and developed a low temperature thermoelectric generator (TEG) using engine water coolant of light-duty vehicles. Experimental results from test vehicle, of which engine size is about 2.0 liters, show that fabricated prototype Thermoelectric Generator generates more than 75W for driving condition of 80 km/hour, and output power is about 28W during idle condition. The proposed TEG can replace conventional radiator without additional water pumps or mechanical devices except for basic components of legacy water cooling system of radiator.